Study of occupational accidents occurred in one of the uranium mines in the central region of Iran during 2006-2010 - GH Halvani; M Ebrahimzadeh; R Nabi Meybodi; F Forooghi Nasab (طب کار)
Background: With increasing activities in underground mines and special risks of such mines, establishment of a coordinated and systematic safety system is important. Prediction of occupational accidents to prevent their occurrence is very important. Methods: In this cross-sectional study, the accidents occurred during 2006 to 2010 in one of the mines of central region of Iran were studied, and the relationship between the causes of accidents and its location, type of injury and injured organs, work experience, age groups, time of accident and work shifts were determined. Data were analyzed by SPSS 16. Results: Mean age of the subjects with accidents was 27.33±4.51 years and their work experience was between 1-3 years, the most frequent accident type included falling objects (24.85%) and contact with moving objects (20.9%). The most common cause of accidents was lack of control measures and the work environment and recklessness. Contusion and sprain (32.2%) and fractures (22.6%) were the most frequent outcome of events. Conclusion: In the present study, indices of repetition severity and frequency of the incident in 2010 were the most frequent ones which is the development of mining operations and the hazards faced by workers. The implementation of safety systems and education of personnel about safety rules is essential in order to prevent accidents, improve safety culture and reduce accident costs.